NORMAL AND PATHOLOGICAL CONDITIONS IN CHILD DEVELOPMENT - Yulduzoy Olimovna Ergasheva; Farog’at Olimovna Ergasheva; Shaxnoza Abduvoitovna Rakhmonova; Sardorbek Yigitaliyev (Modern American Journals, 2025)
This article analyzes both normal (physiological) and pathological (disease-causing) conditions observed during the process of child development. It discusses the key characteristics of normal growth and identifies the main deviations that indicate pathological states. The paper also outlines the fundamental criteria for distinguishing between normal and abnormal developmental patterns according to different age stages. Furthermore, it presents a developmental chart that reflects the typical progression of physical, psychological, and social aspects in children. Preventive measures aimed at ensuring healthy development and early identification of disorders are also highlighted. The study emphasizes the importance of early diagnosis, regular medical observation, and parental awareness in promoting balanced and healthy child growth.
Keywords: Child development, normal growth, pathological conditions, developmental stages, prevention.